SMARCB1-deficient myoepithelial carcinoma of the lung: A case report - Makoto Yoshida; Daisuke Yamashita; Hiroshi Hamakawa; Yutaka Takahashi; Hisateru Yasui; Masato Komatsu; Chiho Ohbayashi; Shigeo Hara (Elsevier, 2020)
A 45-year-old Japanese female with no previous history of neoplastic disease presented with an asymptomatic solid mass in the lower lobe of the right lung, which was detected on chest computed tomography (CT). Pathologic evaluation of a CT-guided needle biopsy specimen revealed epithelioid tumor cells with myoepithelial differentiation. A right lower lobectomy was performed. The specimen was a solid mass measuring 35 × 30 × 20 mm3. Histopathological examination revealed proliferation of large epithelioid and polygonal cells with rhabdoid features and mitotic activity (5cellsper10highpowerfields). Tumor had metastasized to the lymph nodes of the lung hilum. Immunohistochemical studies revealed myoepithelial differentiation as indicated by detection of calponin, α-smooth muscle actin (SMA), muscle actin (HHF-35), EMA and p63. Cytokeratin AE1/3, desmin, WT1, TTF-1, CD34, GFAP and S100 were not detected. Interestingly, switch/sucrose non-fermentable (SWI/SNF)-related, matrix-associated, actin dependent regulator of chromatin, subfamily b, member 1 (SMARCB1) was not detected in any of the tumor cells. Fluorescence in situ hybridization analysis using a dual-color break-apart probe to detect EWSR1 revealed no significant split signal. The final diagnosis was primary pulmonary myoepithelial carcinoma. This report documents the first case of SMARCB1-deficient pulmonary myoepithelial carcinoma with rhabdoid morphology. Additional cases are needed in order to delineate the molecular and prognostic characteristics of SMARCB1-deficient pulmonary myoepithelial carcinoma.